Fatores associados a saúde intestinal de pacientes bariátricos no contexto da pandemia da covid-19 no Brasil - BRASIL, Thalya Cristina Ribeiro (2023)
Introduction: Obesity is a chronic disease that has been affecting more and more people around the world, considered a public health problem, the most effective treatment for severe cases is bariatric surgery, where gastric reconstruction is performed, providing weight loss and consequent improvement in the nutritional status and health of the patient. Objectives: To analyze the factors associated with the intestinal health of bariatric patients in the context of the COVID19 pandemic. Materials and Methods: Analytical and descriptive crosssectional study carried out with bariatric patients over 18 years of age, in the context of the COVID19 pandemic, data collection was performed through the application of forms made available remotely. Results: The study was carried out with 412 participants, from it, it was observed that the majority are female, with complete high school and family income above seven minimum wages, it was also observed that the public had more than three years of surgery bariatric and even consuming healthier foods, the presence of processed and ultraprocessed foods was still very common, with regard to intestinal health, most participants had stools with normal consistency, however, the nonconsumption of fresh fruits was related to worsening bowel function, as well as the duration of surgery and the technique used. Conclusion: The intestinal health of bariatric patients, from the characterization of the type of feces, was associated with factors such as: the nonconsumption of fresh fruits, surgery time and surgical technique used.